DINAMIKA HUKUM KELUARGA ISLAM DI INDONESIA: ANTARA TRADISI, SYARIAH, DAN HUKUM POSITIF - Ilyas, Sufyan (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2024)
This study adopts a qualitative approach to explore and analyze the dynamics of Islamic family law in Indonesia, focusing on the interaction between tradition, Sharia, and positive law. The qualitative approach allows the researcher to delve deeply into the phenomena occurring on the ground, as well as understand the socio-cultural context that influences the implementation of Islamic family law in Indonesian society. The study aims to uncover the perspectives of society, legal practitioners, and scholars regarding the application of Sharia principles in family law cases such as marriage, divorce, and inheritance, as well as the role of positive law in handling family disputes that intersect with Islamic law. Data collection involves in-depth interviews with Sharia law experts, religious court practitioners, and individuals directly involved in Islamic family law practices. Additionally, participatory observation is conducted to comprehend the interaction between the parties involved in family law cases, as well as how religious courts handle family law matters. Relevant legal documents, such as the Compilation of Islamic Law (KHI), fatwas from the Indonesian Ulema Council (MUI), and court decisions related to family disputes, are also analyzed to understand how positive law in Indonesia reflects Sharia values in handling family law cases and how the integration of both legal systems can be improved to achieve justice in alignment with religious and cultural values.